The role of CD8 PET imaging in guiding cancer immunotherapy - Zhang, Jiani; Du, Bulin; Wang, Yuxiang; Cui, Yan; Wang, Shu; Zhao, Yuxuan; Li, Yaming; Li, Xuena (Frontiers in Immunology, 2024)
Currently, immunotherapy is being widely used for treating cancers. However, the significant heterogeneity in patient responses is a major challenge for its successful application. CD8-positive T cells (CD8 + T cells) play a critical role in immunotherapy. Both their infiltration and functional status in tumors contribute to treatment outcomes. Therefore, accurate monitoring of CD8 + T cells, a potential biomarker, may improve therapeutic strategy. Positron emission tomography (PET) is an optimal option which can provide molecular imaging with enhanced specificity. This review summarizes the mechanism of action of CD8 + T cells in immunotherapy, and highlights the recent advancements in PET-based tracers that can visualize CD8 + T cells and discusses their clinical applications to elucidate their potential role in cancer immunotherapy.